1990
DOI: 10.1115/1.2929645
|View full text |Cite
|
Sign up to set email alerts
|

The Measured Energy Impact of Infiltration in a Test Cell

Abstract: Infiltration is customarily assumed to increase the heating and cooling load of a building by an amount equal to the mass flow rate of the infiltration times the enthalpy difference between the inside and outside air—with the latent portion of the enthalpy difference sometimes neglected. Calorimetric measurements conducted on a small test cell with measured amounts of infiltration introduced under a variety of conditions show convincingly that infiltration can lead to a much smaller change in the energy load t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1993
1993
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…After that model was benchmarked by comparing its predations against the model of Buchanan and Sherman [16], and experimental data [19], it was used to investigate the thermal performance of the diffusive building envelope. In that study [18], numerical simulations were carried out to determine the contribution of air infiltration to the heat gain/loss through the "diffusive layer" representation of the building envelope.…”
Section: Introductionmentioning
confidence: 99%
“…After that model was benchmarked by comparing its predations against the model of Buchanan and Sherman [16], and experimental data [19], it was used to investigate the thermal performance of the diffusive building envelope. In that study [18], numerical simulations were carried out to determine the contribution of air infiltration to the heat gain/loss through the "diffusive layer" representation of the building envelope.…”
Section: Introductionmentioning
confidence: 99%
“…From the 1970s onwards, its impact on energy performance has been recognized in the literature, e.g., [1]. Several studies have presented estimations of the heat load fraction in a building that takes place due to infiltration [2][3][4][5][6][7][8][9][10]. In addition, infiltration has been verified as playing an important role in the internal environment and in the indoor air quality [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Claridge et al (1985) reported a calculated overall house energy loss factors 50% above those obtained through regression analysis of recorded experimental house data; indicating a "Heat Recovery" in infiltration energy. Other similar work includes Claridge and Bhattacharyya (1990) who measured infiltration loads equivalent to as low as 20% of those calculated using classical infiltration calculation methods. Classical methods for calculating the additional energy load due to infiltration, including computer models and hourly simulation programs, assume a load increase due to infiltration equal to the infiltrating air mass flow rate times the inside-outside air enthalpy difference.…”
Section: Fire Placementioning
confidence: 99%
“…The heat load is therefore calculated as a summation of the heat loss due to conduction and the heat loss due to infiltration (Claridge and Bhattacharyya, 1990;Claridge and Liu, 1996). A handful of combined heat loss models where therefore proposed to account for this interaction between conduction and infiltration; including Anderlind (1985), Liu (1987), Bailly (1987) and Arquis (1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation